2011
DOI: 10.1002/lary.21864
|View full text |Cite
|
Sign up to set email alerts
|

Meta‐analysis of minimally invasive video‐assisted thyroidectomy

Abstract: This study demonstrates that MIVAT is as safe as the existing gold standard operation. Furthermore, it has better cosmetic and pain outcomes for patients when compared to conventional surgery. MIVAT is a promising new technique, with obvious benefits over the established surgery, for small-volume thyroid disease that mainly affects a young female patient population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 26 publications
3
29
0
Order By: Relevance
“…Five meta-analyses have so far been conducted that have evaluated this comparison in the literature. [5][6][7][8][9] These studies collectively suggest that smaller scars yielded by minimally invasive video-assisted thyroidectomy are more cosmetically favourable than longer scars yielded by conventional thyroidectomy. To determine cosmetic favourability, the studies examined in these meta-analyses had patients rate the acceptability of their own scars on a 10-point scale, without a frame of reference to compare their own scars against.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Five meta-analyses have so far been conducted that have evaluated this comparison in the literature. [5][6][7][8][9] These studies collectively suggest that smaller scars yielded by minimally invasive video-assisted thyroidectomy are more cosmetically favourable than longer scars yielded by conventional thyroidectomy. To determine cosmetic favourability, the studies examined in these meta-analyses had patients rate the acceptability of their own scars on a 10-point scale, without a frame of reference to compare their own scars against.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] The major proposed benefit of the endoscopic approach is that it yields superior cosmetic results when compared to the open approach in select patients. [5][6][7][8][9] Despite this benefit, open thyroidectomy, through an anterior cervical incision, remains the predominant surgical approach in most centres.…”
Section: Introductionmentioning
confidence: 99%
“…While this has been demonstrated by many (7,27) studies, others concluded that a shorter cervical scar was not associated with improved patient satisfaction (36)(37)(38). Furthermore, it may be argued that shorter incisions may compromise the safety of a procedure without favorably influencing patient satisfaction (39).…”
Section: Mivat's Advantagesmentioning
confidence: 98%
“…The two advantages of MIVAT over CT that bring about improved patient satisfaction are its improved pain and cosmetic outcomes (27). A recent meta-analysis demonstrated that MIVAT patients experienced less pain during the entire postoperative period (7).…”
Section: Mivat's Advantagesmentioning
confidence: 99%
“…[6][7][8]10,11 Previous meta-analyses based on these RCTs have reiterated the cosmetic advantage of MIVAT over CT [26][27][28][29] but the abovementioned heterogeneity in wound closure, timing of scar assessment, variety and lack of validation of assessment tools should be borne in mind when interpreting these results. One review article 30 acknowledged this, limiting its meta-analysis of 3/5 RCTs.…”
Section: Randomised Controlled Trialsmentioning
confidence: 99%